Effect of Cryopreserved Placenta Preparations on Peroxidative Indices in Patients with Stenocardia - Shepit’ko, K. V. (Problems of Cryobiology and Cryomedicine, 2004)
Transplantation of cryopreserved placental tissue (CPT) and placenta extract influences the major pathogenic atherosclerosis link, that manifests in the reduction of total cholesterol level, cholesterol of low-density lipoproteids, the atherogeneity coefficient, freeradical oxidation; rise of the level of cholesterol of high density lipoproteids and activation of antioxidant enzymes in blood serum.